A simulator evaluation of effects of assistive technologies on driver cognitive load at railway-level crossings. (30th June 2016) - Larue, Grégoire S.; Rakotonirainy, Andry; Haworth, Narelle L.
ABSTRACT: Intelligent Transport Systems (ITS) have the potential to substantially reduce the number of crashes caused by human errors at railway-level crossings. However, such systems could overwhelm drivers, generate different types of driver errors, and have negative effects on safety at level crossing. The literature shows an increasing interest for new ITS for increasing driver situational awareness at level crossings, as well as evaluations of such new systems on compliance. To the authors' knowledge, the potential negative effects of such technologies have not yet been comprehensively evaluated. This study aimed at assessing the effect of different ITS interventions, designed to enhance driver behavior at railway crossings, on driver's cognitive loads. Fifty-eight participants took part in a driving simulator study in which three ITS devices were tested: an in-vehicle visual ITS, an in-vehicle audio ITS, and an on-road valet system. Driver cognitive load was objectively and subjectively assessed for each ITS intervention. Objective data were collected from a heart rate (HR) monitor and an eye tracker, whereas subjective data was collected with the NASA Task Load Index (NASA-TLX) questionnaire. Overall, results indicated that the three trialed technologies did not result in significant changes in cognitive load while approaching crossings.